2019
DOI: 10.1002/advs.201801982
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Photoactivatable Hsp47: A Tool to Regulate Collagen Secretion and Assembly

Abstract: Collagen is the most abundant structural protein in mammals and is crucial for the mechanical integrity of tissues. Hsp47, an endoplasmic reticulum resident collagen‐specific chaperone, is involved in collagen biosynthesis and plays a fundamental role in the folding, stability, and intracellular transport of procollagen triple helices. This work reports on a photoactivatable derivative of Hsp47 that allows regulation of collagen biosynthesis within mammalian cells using light. Photoactivatable Hsp47 contains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 46 publications
(80 reference statements)
2
27
0
Order By: Relevance
“…The uptake of Hsp47 was tested in fibroblast (NHDF from human skin dermis, L929 from mouse adipose tissue and MEF from mouse embryos), epithelial (HaCaT, human epidermal keratinocytes) and endothelial (HDMEC from human dermis) skin cells. A recombinant EGFPtagged Hsp47 (hereafter referred to as H47 [23]) was used for these studies. The different cell types were seeded at same cell density and incubated with H47 at concentrations between 0.1 µM and 1.0 µM.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The uptake of Hsp47 was tested in fibroblast (NHDF from human skin dermis, L929 from mouse adipose tissue and MEF from mouse embryos), epithelial (HaCaT, human epidermal keratinocytes) and endothelial (HDMEC from human dermis) skin cells. A recombinant EGFPtagged Hsp47 (hereafter referred to as H47 [23]) was used for these studies. The different cell types were seeded at same cell density and incubated with H47 at concentrations between 0.1 µM and 1.0 µM.…”
Section: Resultsmentioning
confidence: 99%
“…We recently demonstrated that uptake of exogenous Hsp47 could specifically enhance collagen deposition in fibroblast cultures [23]. Uniquely, Hsp47 is a collagen-specific chaperone.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations